RHIZOSPHERE FUNGI OF GUNUNG HALIMUN NATIONAL PARK - Suharna, Nandang (BERITA BIOLOGI, 2001)
An ecological study was conducted to assess the occurrences of rhizosphere fungi in three dominating trees (Altingia excelsa, Schima wallichii and Castanopsis javanica) within Gunung Halimun National Park.Rhizosphere trees in Gunung Halimun National Park was mainly dominated by Trichoderma (47%), followed by Penicillium (16%), Cunninghamella (10%),Mortierella (15%),Acremonium (7%), and Humicola (6%).Similar composition of rhizosphere fungi was shown by the three trees and mainly consisted of Trichoderma and Penicillium.There was negative correlation of rhizosphere to fungal composition which was shown by C.javanicus and the positive correlation was shown by A. excelsa and S. wallichii.Based on total of fungi encountered, Trichoderma was found to be the most common and dominant fungus in rhizosphere of those trees.Other fungi were also considered common were Penicillium, Mortierella, Cunninghamella, Acremonium and Humicola. Based on the number of samples, the frequency of the occurrence of Trichoderma was the highest (100%), followed by Penicillium (88%),Cunninghamella (59%), Humicola (47%), Acremonium (41%), Mortierella (35%), Verticillium (18%), Cylindrocladium (12%), Aspergillus (6%), and Gliocephalotrichum (6%).